(untitled) (Global Journal of Human-Social Science, 2013)
The paintings of Giuseppe Archimboldo 1527-1593 populate the imaginations of children and adults of all times allowing the distance from the look of your images the visualization of new figures generating curiosity or even strange I tried to understand the relationships established between youth identities and their creative expressionsportraits and self portraits - artistic embodied in threedimensional structures which served as sources of research on teaching Drew up a proposal for readings and compositions plastic three-dimensional elements of nature or industrially produced selected and collected by the students of 5th and 6th grades in the subject of Visual Arts an elementary school in RS Brazil in 2007 Producing pictures full of visual sensory appeals to the touch and smell students recreating elements of everyday life curious figures exotic and inquisitive which express their identity forms